PENGELOLAAN HUTAN MANGROVE BERBASIS MASYARAKAT DI DESA BUDENG, KECAMATAN JEMBRANA, KABUPATEN JEMBRANA - Ginanjar, Ujang Rija; Adnyana, I Wayan Sandi; Sudarma, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 16 No 2 (2022), 2022)
The mangrove forest in Budeng Village is managed by local communities by forming farmer groups. The interaction of the people of Budeng Village in mangrove management, this will determine the sustainability of the mangrove area in the future. It is necessary to have the right strategy in mangrove management by following the rules of balance and sustainability. The purpose of this study is to analyze changes in mangrove forest cover, find out the perception and participation of the community in mangrove forest management and develop an ideal mangrove forest management strategy. Data collection includes using literal studies, observations, questionnaires and Forum Group Discussion. Samples in this study was 30 people. Data analysis was performed using SWOT matrix and QSPM matrix. The condition of mangrove forests in Budeng Village is relatively good, there is an increased in mangrove forest cover covering an area of 36 ha in the period from 2016 to 2021. The level of community perception in mangrove forest management excellent categories and the level of community participation is in high categories. The general strategy on mangrove forest management in Budeng Village is growth strategy. Based on the results of the SWOT analysis, there are 14 alternative strategies for mangrove forest management in Budeng Village with a priority strategy based on the results of the Total Attractiveness Score calculation is to increase the role and commitment of local governments in mangrove forest management in Budeng Village. Keywords: mangroves; perception; participation; strategy; management